DRE: Drug Set Enrichment Analysis - Pan, Lu (SciLifeLab Serve, 2026)
This app is part of the Drug Repurposing Encyclopedia (DRE), a web server for systematic drug repurposing across 20 organisms. Refer to https://doi.org/10.1101/2023.03.10.532084 for the paper describing the tool.